1990
DOI: 10.1002/art.1780330520
|View full text |Cite
|
Sign up to set email alerts
|

A summary of the impact of musculoskeletal conditions in the united states

Abstract: We report here a summary of the economic and social impact of musculoskeletal conditions in the United States. The economic cost of musculoskeletal conditions approaches 1% of the gross national product (GNP) each year. The literature on this subject is rapidly expanding, in part, to reflect the growing prevalence of musculoskeletal conditions due to the aging of the population, as well as a declining mortality rate. Accordingly, at the request of the National Arthritis Data Task Force, we analyzed the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 4 publications
0
37
0
Order By: Relevance
“…In adults, inflammatory arthritis is known to have a massive economic impact (1)(2)(3)(4). Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, inflammatory arthritis is known to have a massive economic impact (1)(2)(3)(4). Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that musculoskeletal disorders have a great impact on individuals and society because of their high prevalence, morbidity and disability potential, and large use of acute and long-term health care and support resources (1,2). Rheumatoid arthritis (RA) represents the paradigm of chronic inflammatory musculoskeletal disorder with a high prevalence and a progressive clinical course negatively affecting patients' quality of life, function, and life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…In 1989 and 1990, the National Arthritis Data Work Group published 2 articles summarizing the economic impact of musculoskeletal conditions in the United States, as well as the extent of medical care system usage, activity limitation, and work loss associated with these conditions (1,2). In the more comprehensive of the 2 reports (l), studies using national, community-based sampling frames as well as those using clinical sampling frames were reviewed.…”
mentioning
confidence: 99%